Three‐dimensional T2‐weighted imaging for liver MRI: Clinical values of tissue‐specific variable refocusing flip‐angle turbo spin echo imaging. Issue 2 (8th January 2014) - Takayama, Yukihisa; Nishie, Akihiro; Asayama, Yoshiki; Ushijima, Yasuhiro; Fujita, Nobuhiro; Shimamoto, Dai; Yoshiura, Takashi; Obara, Makoto; Takemura, Atsushi; Yoneyama, Masami; Honda, Hiroshi
<x xml:space="preserve">Abstract</x> Purpose To assess the clinical utility of tissue‐specific variable refocusing flip‐angle (VRFA) turbo‐spin echo imaging for three‐dimensional T2‐weighted imaging (3D‐T2WI) of the liver. Materials and Methods Fifty‐nine patients were scanned with three types of fat‐suppressed T2WI for the comparison: two‐dimensional single‐shot turbo spin echo T2WI (ssT2WI), 3D‐T2WI with tissue‐specific VRFA (VISTA‐TSV), and 3D‐T2WI with low‐constant VRFA (VISTA). Qualitatively, artifacts in the left and right lobes of the liver and black‐blood effects in the liver were compared using the Wilcoxon signed‐rank test with the Bonferroni correction. The detection and correct characterization rates of liver lesions were compared using McNemar's test. Results VISTA‐TSV showed reduced artifacts in the left and right lobes of the liver compared with VISTA (P < 0.017). The artifacts shown by VISTA‐TSV were equivalent to those shown by ssT2WI. The black‐blood effects of VISTA‐TSV and VISTA were better than that of ssT2WI (P < 0.017). VISTA‐TSV showed the best detection and correct characterization rate of liver lesions among the three imaging techniques (P < 0.05). Conclusion 3D‐T2WI with tissue‐specific VRFA can reduce artifacts of the liver, sufficiently suppress the signal in blood vessels, and has a potential to improve the detection and correct characterization rates of liver lesions. J. Magn. Reson. Imaging 2015;41:339–346.© 2013 Wiley Periodicals, Inc.